Ciberespaço e espacialidades dos corpos gordos de homens gays no contexto de Florianópolis – SC - Nunes, Diego Miranda (2024)
The connected, wireless life, driven by technological advances and the emergence of the internet, gives rise to this research. Living online on social media, staying updated with news virtually, and using dating apps are symptoms of contemporary culture, known as cyberculture. This culture imperatively traverses our bodies, shaping our ways of being and existing in cyberspace. Thus, this study aims to understand how spatialities are produced through the performativity of fat gay men in affective-sexual relationships mediated by the Grindr app in Florianópolis – SC. We interviewed ten gay men who self-identify as fat. By doing so, we bring fat bodies to the center of the geographic academic debate, filling a gap that Brazilian geographic science had yet to explore, unlike Anglophone geography, which has included this theme in its agenda since the early 2000s. Moreover, we propose a specific focus on these bodies through a dating app, Grindr, launched in 2009, which has gained popularity within the LGBTQIAPN+ community, with a predominance of men who have relationships with other men. Florianópolis was chosen as the focus of the research due to its place in a tourism circuit for this community, in addition to being among the five most welcoming capitals, receiving the gay-friendly seal. Despite this title, the capital of Santa Catarina is not exempt from urban problems and violence, like other metropolises. The "island of magic," as it is affectionately known, also resists conservative waves that attempt to disassociate the LGBTQIAPN+ community from the city. In this context, the fat bodies of gay men in cyberspace draw our attention, not only for their spatialities but also for the understanding that these bodies bear marks in time and space. From childhood, through adolescence to adulthood, fat bodies are marginalized, seen as careless, and face prejudice manifested in medical discourse and the media, which attempts to impose a standardized body type. Challenging these established standards is also a goal of this study, recognizing that fat bodies exist and resist in spaces not designed for them. Our eight methodological steps, along with in-depth interviews and Discursive Textual Analysis, allowed us to understand that these bodies are unique and produce spatialities based on their experiences. Additionally, staying in the virtual space involves agreements, negotiations, and strategies. Through performativity, these subjects engage in a continuous process of repetition, subverting the socially and virtually imposed order. The performative acts manifested in how these subjects behave in cyberspace determine their permanence and effectiveness on Grindr.